Evaluating Needle Sticks and Sharp Object Injuries in Developing Country: A Diagnostic Institute in Dominican Republic - Taveras, Michelle; Barach, Paul (International Journal of Infection Control, 2009)
The goal of the study is to review the impact of sharp object injuries to healthcare professionals in a developing country in order to prevent them. A cross-sectional survey was conducted in an advanced diagnostic and imaging hospital. Out of 350 healthcare workers, 100 were randomly enrolled in the study and did not use any restrictions in randomization. Incomplete surveys were discarded. 71 surveys were considered for this study. The survey consisted of 9 questions focusing on sharp object injuries. The questionnaire was intended to identify which group of healthcare workers had the highest risk of exposure and what types of sharp objects they were being exposed to. Interviews were also conducted. It was piloted with laboratory technicians. During the pilot, no changes were made to the questionnaire. Of those surveyed (n=71), 21% reported exposure to sharp object injuries over their period of employment at the diagnostic institute. Needle stick injuries were the most common type of injury. Laboratory technician was the job category with the most reported exposures. There is a 29% probability that a staff member will come in contact with an infectious disease every year through sharp object injuries. Recommendations to decrease sharps exposure include creating a computerized reporting process called Sharps Injury Reporting Process, building an infectious disease committee, implementing safety instrumentation while addressing the issue of cost, surveying staff every 6 months, and increasing administration involvement.